The Effect of 3 Colored Chronographic Paper on Decline of Interdialytic Weight Gain in Chronic Hemodialysis Patients - Seemok, Phadungchat (Journal of Health Science of Thailand, 2018)
Over interdialytic weight gain leading to one common and serious complication that is hypotension during chronic hemodialysis. Despite conventional advisory from certified hemodialysis personnel some of the patients fail to properly control their interdialytic weight gain. The 3 colored chronographic paper was created as a tool to convince those patients to realize their ever-changing status and why the over interdialytic weight gain harm them during the dialysis session. The interdialytic weight gain of ณ 3 kg. means danger and was plotted in red zone, the interdialytic weight gain of ณ 2-3 kg. means to beware of danger and was plotted in yellow zone and the interdialytic weight gain of ฃ2 kg. means safety was plotted in green zone. After the 3 colored chronographic paper were used at 1,6 and 12 months, the changes of interdialytic weight gain of those patients were observed. First, 20 patients in red zone weight were included and one was excluded later. Of the 19 patients, at 1 month, 5.3 percent changed into yellow zone, at 6 months 15.8 percent changed into yellow and green zones and at 12 months 52.6 percent changed into yellow and green zones. It was concluded that the 3 colored chronographic paper together with conventional advisory may help the over interdialytic weight gain patients to realize and try to adapt their eating and drinking habits in order to control their interdialytic weight gain.